Criminal responsibility and legal capacity - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
Determining whether a person has legal capacity and criminal responsibility is the main task of forensic psychiatry. In order for a person to have legal capacity and/or criminal responsibility, they must be able to understand their actions. Mental illnesses and young age are factors that affect both legal capacity and criminal responsibility. The insanity defense is based on the principle that a person who cannot appreciate the nature of the crime due to a mental illness they had when they committed the crime, cannot distinguish right from wrong and therefore is not legally responsible for the crime. Schizophrenia and similar psychoses and affective disorders are the leading mental disorders affecting both criminal responsibility and legal capacity. In the evaluation of criminal responsibility in children, it is important to determine the minimum legal age for criminal responsibility and to take biopsychosocial development factors into account. In a forensic mental assessment, not only is the psychiatric history and mental disorders evaluated, but also a mental status examination, including attention, mood, thinking (form and structure), memory and cognitive function, is made. A basic approach to assessment of mental state of a person in accordance with medical ethics is discussed in this chapter. © 2021 Nova Science Publishers, Inc.